Are You Ready for a Story? Kindergarten Children's Emotional Competencies during a Story-Reading Situation Is Associated with Their Readiness for School - Inbar Sofri; Amanda Czik; Yair Ziv (MDPI AG, 2023)
The current study aimed to explore the associations between children's emotional reactions to stories and their school readiness skills. One hundred and fifty kindergarten children (Mage = 66.98 months; 66 boys) were interviewed to examine their emotional reactions to a story, and the children's kindergarten teachers reported on the children's school readiness skills: verbal abilities, approaches toward learning, and social skills. Using bibliotherapeutic terms and methods, the children's identification with the main character in the story, their insight about the story, and their ability to connect the story to their own experiences were coded. Findings revealed associations between the children's emotional responses to the story, specifically, the children's identification and echoing with all three school readiness indicators (verbal abilities, behavior, and approaches toward learning). Additionally, the children's insight into the story mediated the link between verbal abilities and approaches toward learning and between verbal abilities and hyperactivity. Practically, the current study offers a new approachable method that practitioners can use as a possible emotional tool in early education. Children's responses to a story can provide a unique opportunity to better understand children's perceptions of different narratives and socio-emotional situations, which can direct educators in their work. Empirically, the current study can guide further research and training on utilizing stories to understand children's readiness for school.